Leveraging renewable energy for Türkiye's future hydrogen supply chain - Tuerkali-Ozbek, Busenur; Erdogan, Ahmet; Guler, Mehmet Guray (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
As energy and climate crises necessitate a shift to sustainable resources, hydrogen - with its zero-emission potential-is expected to play a key role in the energy transition. Designing an effective hydrogen supply chain (HSC) is essential to realizing this potential. This study introduces a multi-period, multi-objective stochastic optimization model for T & uuml;rkiye's transportation-sector HSC. It addresses gaps in existing research by integrating dynamic renewable energy availability, lifecycle-based CO2 emissions, and regional green hydrogen prioritization. The epsilon-constraint method is used to balance economic and environmental objectives. Results show that T & uuml;rkiye can significantly reduce emissions by gradually transitioning from fossil-based production and by optimizing facility locations based on regional solar, wind, and hydrogen sulfide potential. Centralized production reduces costs but increases transport risk and emissions, while localized production improves resilience yet may increase fossil fuel reliance in resource-limited regions. These findings offer strategic guidance for aligning hydrogen planning with T & uuml;rkiye's climate commitments.
Keywords: Hydrogen supply chain; Renewable energy; Stochastic programming; Carbon footprint; Chemistry; Electrochemistry; Energy & Fuels